Glucosamine‐Conjugated Nanoparticles for the Separation of Insulin‐Secreting Beta Cells. Issue 9 (8th March 2013) - Narayanan, Karthikeyan; Lin, Alex W. H.; Zheng, Yuangang; Erathodiyil, Nandanan; Wan, Andrew C. A.; Ying, Jackie Y.
<x xml:space="preserve">Abstract</x> A small molecule, glucosamine, is used as targeting moiety for insulin‐secreting beta cell separation in artificial cell mixtures and tissue samples. The specificity of glucosamine allows it to be used in cell sorting applications. In addition, a thrombin‐specific cleavable peptide was used as an intermediary to release nanoparticles from cell surfaces to facilitate cell attachment and proliferation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>